MEK inhibitors reverse resistance in epidermal growth factor receptor mutation lung cancer cells with acquired resistance to gefitinib. Issue 1 (13th October 2012) - Huang, Ming-Hung; Lee, Jih-Hsiang; Chang, Ya-Ju; Tsai, Hsin-Hui; Lin, Yu-Lin; Lin, Anya Maan-Yuh; Yang, James Chih-Hsin
Abstract : Lung adenocarcinoma cells harboring epidermal growth factor receptor (EGFR) mutations are sensitive to EGFR tyrosine kinase inhibitors (TKIs), including gefitinib. Acquired resistance to EGFR‐TKIs develops after prolonged treatments. The study was prompt to explore effective strategies against resistance to EGFR‐TKIs. We established gefitinib resistant PC‐9 cells which harbor EGFR exon 19 deletion. Known mechanisms for intrinsic or acquired EGFR‐TKI resistance, including KRAS mutation, HER2 mutation, EGFR T790M mutation and MET gene amplification, were studied, and we did not observe any known mechanisms for intrinsic or acquired resistance to EGFR‐TKIs in the resistant cells. In the parental PC‐9 cells, labeled as PC‐9/wt, gefitinib completely inhibited EGF‐induced phosphorylation of EGFR, AKT and ERK. Gefitinib inhibited EGFR phosphorylation, but was unable to block EGF‐induced phosphorylation of ERK in resistant cells, labeled as PC‐9/gef cells, including PC‐9/gefB4, PC‐9/gefE3, and PC‐9/gefE7 subclones. We detected NRAS Q61K mutation in the PC‐9/gef cells but not the PC‐9/wt cells. MEK inhibitors, either AZD6244 or CI1040, inhibited ERK phosphorylation and sensitized gefitinib‐induced cytotoxicity in PC‐9/gef cells. Whereas MEK inhibitors or gefitinib alone did not activate caspases in PC‐9/gef cells, combination of gefitinib and AZD6244 or CI1040 induced apoptosis. Our in vivo studies showed that gefitinib inhibited growth of PC‐9/wt xenografts but not PC‐9/gef xenografts. Furthermore, combination of a MEK inhibitor and gefitinib inhibited growth of both PC‐9/wt xenografts and PC‐9/gefB4 xenografts. To conclude, persistent activation of ERK pathway contributes to the acquired gefitinib‐resistance. Combined treatment of gefitinib and MEK inhibitors may be therapeutically useful for acquired gefitinib‐resistance lung adenocarcinoma cells harboring EGFR mutations. Highlights: ► PC9/gef cells are 270‐fold resistant than PC9 cells to gefitinib. ► PC9/gef cells contain EGFR del 19 mutation but not EGFR T790M or MET amplification. ► NRAS Q61K mutation is found in all PC9/gef cells. ► ERK phosphorylation can not be suppressed by gefitinib in PC9/gef cells. ► MEK inhibitors plus gefitinib inhibit growth of PC9/gef cells in vitro and in vivo .